2017
DOI: 10.1108/jfra-01-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Social responsibility disclosure in Islamic banks: a comparative study of Indonesia and Malaysia

Abstract: Purpose This paper aims to explore social responsibility reporting of full-fledged Islamic banks in two developing countries, namely, Indonesia and Malaysia. Corporate social responsibility (CSR) has become an important aspect of business society. As such, companies have shown a growing interest in reporting their social and environmental initiatives. Design/methodology/approach Content analysis of the annual reports for three full-fledged local Islamic banks in Indonesia and three Islamic banks in Malaysia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 47 publications
4
109
1
13
Order By: Relevance
“…As per the Hexun criteria, the overall CSR score for a specific pharmaceutical firm may be calculated as the following equation: (1) where CSR(SHA), CSR(EMP), CSR(CUST & SUP), CSR(ENV), and CSR(SOC) are corporate fulfillment towards the CSR dimensions of shareholders, employees, customers and suppliers, the environment, and society respectively. The score of each dimension, as well as the overall CSR score, were directly extracted from Hexun CSR rating.…”
Section: Csrmentioning
confidence: 99%
See 1 more Smart Citation
“…As per the Hexun criteria, the overall CSR score for a specific pharmaceutical firm may be calculated as the following equation: (1) where CSR(SHA), CSR(EMP), CSR(CUST & SUP), CSR(ENV), and CSR(SOC) are corporate fulfillment towards the CSR dimensions of shareholders, employees, customers and suppliers, the environment, and society respectively. The score of each dimension, as well as the overall CSR score, were directly extracted from Hexun CSR rating.…”
Section: Csrmentioning
confidence: 99%
“…Corporate social responsibility (CSR) has gained momentum as a critical issue for many firms because of the increase in public awareness about the impact of corporate activities on the environment and society [1]. Companies are expected to act in a socially responsible manner as well as be financially accountable [2].…”
Section: Introductionmentioning
confidence: 99%
“…The variable of total sustainability was used for empirical testing. Consistent with [56], for measuring sustainability scores the following formula was used, i.e., = dj N , where, N means the total number of disclosures while d j are the numbers of discoursers performed by the banks. The formative variable of total sustainability is considered as an endogenous variable by the previous studies [57].…”
Section: Total Sustainability Score (Formative Variable)mentioning
confidence: 99%
“…It represents the total number of members available in the Shariah supervisory committee of the Islamic banks. The author of [11] used the average of SSB, while [56] used the number of SSB members to proxy this variable. This study will use the log of the total number of Shariah scholars on the board.…”
Section: Shariah Supervisory Board Size (Ssbs)mentioning
confidence: 99%
“…Many previous studies examined voluntary disclosure in annual reports of Islamic financial institutions in different countries ( Amran et al (2017) found that CSR reporting of Islamic banks has generally increased in both Malaysia and Indonesia. More precisely, workplace and society dimensions were found to be the most commonly reported areas by Islamic banks in both countries.…”
Section: Literature Reviewmentioning
confidence: 99%